How to choose your victim - Abbink, Klaus; Doğan, Gönül (Games and economic behavior, 2019)
We introduce the experimental mobbing game. Each player in a group has the option to nominate one of the other players or to nominate no one. If the same person is nominated by all other players, he loses his payoff and the mob gains. We conduct three sets of experiments to study the effects of monetary gains, fear of being mobbed, and different types of focality. In the repeated mobbing game, we find that subjects frequently coordinate on selecting a victim, even for modest gains. Higher gains make mobbing more likely. We find no evidence that fear of becoming the victim explains mobbing. Richer and poorer players are equally focal. Pity plays no role in mobbing decisions. Ingroup members – introduced by colours – are less likely to be victims, and both payoff difference and colour difference serve as strong coordination devices. Commonly employed social preference theories do not explain our findings.